Character Education in 21st Century Learning in Indonesia - Wija Astawa, Dewa Nyoman; Sadri, Ni Wayan; Bayu Temaja, I Gede Bagus Wisnu (Westscience Press, 2025)
Character education is one of the important aspects in the learning process in schools, which aims to form positive attitudes and behaviors in students. This article aimed to explore the implementation of character education in Indonesian schools and the challenges faced in its implementation. This study used a qualitative approach with interview methods and observations of teachers, students, and other related parties in several elementary schools. The results showed that character education in schools has been well received by most students, but in practice there are a number of obstacles, such as limited lesson time given to academic materials and lack of consistency in the application of character values. In addition, student resistance to character-based learning is also one of the obstacles that must be overcome. Furthermore, the use of technology in character learning is seen as an effective tool to attract students’ attention and enrich learning methods. The role of teachers is very vital in the success of character education, therefore in-depth teacher training related to the implementation of character in the curriculum that is more relevant to the development of the times is needed. Finally, collaboration between schools, parents, and the community is an important factor in supporting the success of sustainable character education. Therefore, there needs to be increased synergy between related parties to produce the next generation of the nation with strong character and adaptive in facing the challenges of the times.